Mesonephric-like Adenocarcinoma Arising from the Ovary: A Case Review and Treatment Considerations - Horibe, Yu; Kanno, Toshiyuki; Motohashi, Takashi; Akizawa, Yoshika; Funamoto, Hiroshi; Tabata, Tsutomu (Thai Journal of Obstetrics and Gynaecology, 2024)
Mesonephric-like adenocarcinomas (MLAs) are a rare classification of pathologic cancers. These clinically high-grade cancers exhibit a distinct propensity for distant metastasis, notably in the lungs, often diagnosed at advanced stages (II–IV) according to The International Federation of Gynecology and Obstetrics (FIGO), and clinical course is unclear. A 62-year-old woman was diagnosed as a left ovarian tumor, magnetic resonance imaging (MRI) revealed a 68 mm nodule confined to the left ovary with no evidence of pelvic cavity invasion. After surgery, the patient was diagnosed with FIGO stage IIIA1(ii) mesonephric-like adenocarcinoma. Homologous recombination deficiency (HRD) status and breast cancer 1/2 (BRCA1/2) were negative. Postoperatively, the patient received six sessions of taxotere and cyclophosphamide (TC) chemotherapy as an adjuvant chemotherapy with no recurrent lesions. There are few reports that the positive rate of HRD score and the efficacy of poly adenosine diphosphate (ADP) - ribose polymerase inhibitors (PARPi) remain unclear. Adjuvant chemotherapy using carboplatin and paclitaxel after complete surgery has shown promising results with a low risk of recurrence. Further accumulation of cases and studies on regimens, including long-term prognosis and maintenance therapy are needed.